Berberine ameliorates testosterone-induced benign prostate hyperplasia in rats - Ehsan Shabani; Heibatullah Kalantari; Mojtaba Kalantar; Mehdi Goudarzi; Esrafil Mansouri; Hadi Kalantar (BMC, 2021)
Abstract Introduction Benign prostatic hyperplasia (BPH) is a major urologic problem that mostly develops in older males. Oxidative stress and inflammation influence the occurrence of BPH. Berberine (BBR) is a natural ingredient that has antioxidant and anti-inflammatory properties. The current research aims at examining the effects of BBR on testosterone-stimulated BPH in rats. Methods Animals were randomly categorized to six groups. In the control group, normal saline and olive oil were injected as the vehicle. BPH group: received testosterone (3 mg/kg, subcutaneous, 28 days), BPH + BBR groups; received BBR (25 and 50 mg/kg, p.o, 28 days), BPH + finasteride groups: received finasteride (1 mg/kg, p.o, 28 days), BBR (50 mg/kg, p.o, alone) was administered for subjects in the BBR group. On the 29th day, after anesthesia, cervical dislocation was used to kill the subjects. Serum concentration of testosterone and dihydrotestosterone was measured and prostate tissues were excised and used for biochemical, inflammation, and histological analysis. Results BBR prevented increased serum concentrations of testosterone and dihydrotestosterone. BBR considerably reduced BPH-stimulated oxidative stress and inflammation through preventing the rise in lipid peroxidation and nitrite concentration and declined the accumulations of pro-inflammatory cytokines (e.g. interleukin 1β and tumor necrosis factor α) and declining the depletion rate of GSH and the function of catalase and superoxide dismutase. Histopathological investigations reported that administration of BBR could suppress testosterone-stimulated BPH. Conclusion This study demonstrated that BBR could significantly prevent the development of BPH in rats.